Economic Growth, Income Distribution, and Poverty in Poland During Transition - Paci, Pierella (World Bank, Washington, D.C., 2013)
The authors attempt to analyze the linkages between macroeconomic policies and economic growth variables, their movement over time, and their impact on poverty in the case of Poland. Poland, a middle-income country, is of particular interest because its data sources allow for a relatively detailed analysis of such developments, and the macroeconomic environment and the economic growth variables show a relatively sizable degree of variance. In addition, Poland has struggled in the past few years to reduce poverty while still experiencing positive economic growth. The authors show that in Poland, poverty-reducing growth depends heavily on the ability of the economy to generate jobs. During the early years of transition, net job growth was positive, while after the Russian crisis of 1998, productivity gains were accomplished mostly through labor shedding, henceforth, increasing poverty in Poland. In addition, the authors identify how fiscal and social protection policies affect income distribution and poverty in Poland.